Operational Audit Of Human Resources (Case Study At PT. Jabarti Abazas Prima) - Sandra, Amelia; Sundarta, M. Imam; Muniroh, Leny (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
This study aims to find out related to employee activities that have been determined, to determine the controls that have been implemented, and to find out whether operational audits of human resources can improve efficiency and effectiveness on the performance of company employees. In order to assess the effectiveness and efficiency of the company's operational activities.The research method used in this study is to use a qualitative approach using descriptive methods where the results of data research are in the form of exposure to the results of the situation that has been studied and presented in the form of narrative variants or recommendations for companies. The data collection used are interviews, observation, documentation and literature study. Assessment of the effectiveness and efficiency of the company obtained from data sources in the form of secondary data, namely the history and development of the company, organizational structure, data on the implementation of human resources and documents related to research and also obtained data sources in the form of primary data, namely financial reports on operational activities and interviews with company manager.The results of the study indicate that the policies contained in the company towards employee activities are in accordance with what has been determined. It can be concluded that the operational activities of human resources at PT. Jabarti Abazas Prima has not been effective and efficient because there are still weaknesses that have resulted in hampering the development of the company.